Developing Vlog-Based History Learning Media to Strengthen Students’ Learning Interest in Vocational High School - Helwin Maulidia; B. Fitri Rahmawati; Muhammad Shulhan Hadi (Universitas Hamzanwadi, 2024)
History learning in vocational schools is often perceived as content-heavy and monotonous, which can reduce students’ attention and willingness to participate. This study aimed to develop a vlog-based learning medium, determine its feasibility, and examine its effectiveness in strengthening the learning interest of grade X students at SMKN 1 Jerowaru. The study employed research and development adapted from the Borg and Gall model and implemented seven stages: needs analysis, planning, preliminary product development, expert validation, initial revision, field testing, and product refinement. Data were collected through expert-validation sheets and pretest-posttest learning-interest questionnaires administered to 23 students in the Graphic Design program. Product feasibility was assessed by material, media, and learning experts, while effectiveness was examined using descriptive percentages, a normality test, and the Mann-Whitney U test. The product achieved feasibility scores of 80.0% from material experts, 76.7% from media experts, and 79.3% from learning experts. Students’ learning-interest score increased from 43% before using the vlog video to 81% afterward. The Mann-Whitney test produced Asymp. Sig. (2-tailed) = 0.000, indicating a statistically significant difference between the pretest and posttest results. These findings show that vlog-based media is feasible and potentially effective for creating a more engaging, contextual, and digitally relevant history-learning experience in vocational high schools.